RISK ANALYSIS OF MAJOR ACTIONS LISTED IN THE STOCK EXCHANGE OF LIMA - Gomero Gonzales, Nicko Alberto (2013)
By nature, the stock market and the shares that it is negotiated, are characterized by their high degree of volatility or risk, which is why investors, it is uncommon to bet on a single asset, on the contrary always bow their preferences to structuring portfolios because this way, product diversification may achieve optimal points of convergence between risk and expected return. There are methods for determining the volatility of an asset, among them is the variance and standard deviation on the other hand can also be used for this purpose the Beta indicator pointing the way to change the actions of market moves, the quantification of these indicators in this article indicate that the stock market can find assets with different degrees of risk.